2010
DOI: 10.1111/j.1471-4159.2009.06516.x
|View full text |Cite
|
Sign up to set email alerts
|

AAV‐mediated chronic over‐expression of SNAP‐25 in adult rat dorsal hippocampus impairs memory‐associated synaptic plasticity

Abstract: Long-term memory is formed by alterations in glutamate-dependent excitatory synaptic transmission, which is in turn regulated by synaptosomal protein of 25 kDa (SNAP-25), a key component of the soluble N-ethylmaleimide-sensitive factor attachment protein receptor complex essential for exocytosis of neurotransmitter-filled synaptic vesicles. Both reduced and excessive SNAP-25 activity has been implicated in various disease states that involve cognitive dysfunctions such as attention deficit hyperactivity disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 59 publications
(141 reference statements)
1
26
0
Order By: Relevance
“…SNAP-25 haploinsufficient mice show no observable phenotypic defects but complete loss of SNAP-25 blocks evoked synaptic transmission [13]. Moreover, overexpression of SNAP-25 inhibits normal calcium responsiveness and can impair memory-associated synaptic plasticity [63]. These findings suggest that modulation of SNAP-25 levels are important for overall SNARE function, especially in generating differences in calcium dependence between neuronal and non-neuronal secretory vesicular fusion events.…”
Section: Discussionmentioning
confidence: 99%
“…SNAP-25 haploinsufficient mice show no observable phenotypic defects but complete loss of SNAP-25 blocks evoked synaptic transmission [13]. Moreover, overexpression of SNAP-25 inhibits normal calcium responsiveness and can impair memory-associated synaptic plasticity [63]. These findings suggest that modulation of SNAP-25 levels are important for overall SNARE function, especially in generating differences in calcium dependence between neuronal and non-neuronal secretory vesicular fusion events.…”
Section: Discussionmentioning
confidence: 99%
“…The retina and the hippocampus were chosen for the study as these are prime targets for AAV delivery to the CNS (Auricchio et al, 2001;Yang et al, 2002;Burger et al, 2004;O'Reilly et al, 2007;McKee et al, 2010;Kay, 2011;Millington-Ward et al, 2011). Recombinant AAV2/5 vectors, each expressing a fluorescent reporter gene, GFP and DsR (AAV-GFP and AAVDsR), were generated.…”
Section: Discussionmentioning
confidence: 99%
“…Two reporter AAVs, each expressing an undivided Living Colors fluorescent protein-encoding gene, have been employed to probe the dynamics of a dual-vector strategy. AAV2 was packaged into a type AAV5 capsid, as this serotype (AAV2/5) has been found previously to efficiently transduce brain neurons (Burger et al, 2004;McKee et al, 2010) and photoreceptors (Auricchio et al, 2001;Yang et al, 2002;O'Reilly et al, 2007). After viral transduction with 1.5 · 10 9 viral particles (VP) of each of the reporter AAVs, approximately one-third of the retinal cells expressed one or both transgenes at levels detectable by native fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…For example, viral overexpression of SNAP-25 in the dorsal hippocampus of young adult rats increases glutamatergic transmission and is sufficient to mediate substantial cognitive deficits. 164 More recent work has shown that downregulation of SERT in rat hippocampus attenuates locomotor activity and impulsivity, suggesting that increased serotonergic transmission within this brain region could potentially ameliorate some symptoms of ADHD. 165 …”
Section: Causal Modellingmentioning
confidence: 99%